Perceived Stress, The Sources, Severity and Coping Mechanisms Among Undergraduate Medical Students in a Pakistani Medical School - Rahman, Dania Khawar; Nadeem, Amina; Riaz, Bushra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the perceived stress, its sources, and severity and evaluated the relationship between causes of perceived stress and their coping mechanisms.Study Design: Cross-Sectional Survey.Place and Duration of Study: Army Medical College Rawalpindi and Fuji Foundation University Medical College, Islamabad Pakistan from Jun 2018 to Jun 2019.Methodology: Four hundred undergraduate medical students of the first and second-year MBBS were included in this study. Voluntary consenting students filled the questionnaires regarding perceived stress, its sources, and severity, along with the coping mechanisms.Results: Among 400 participants, the male and female students were 55.3% and 44.8%, respectively. Three hundred and forty (85%) students were stressed. Perceived stress was not statistically associated with academic stress (p-value=0.77). The coping mechanisms that were found significant were the 'use of tranquillizer' and 'positive reframing' with p-value of 0.018 and 0.025.Conclusion: A higher level of perceived stress was found in the medical students. Mostly the stressors were associated with the academic domain and not related to health and psychosocial domains. The coping mechanism used by the medical students were tranquillizers and positive reframing.